Automatic Skyscraper Window Cleaning System - Kavya S; Karthik M.S.; Arun Kumar C (IAES International Journal of Robotics and Automation (IJRA), 2017)
Automatic Skyscraper Window Cleaning System (ASWCS) aims at providing a risk free and more automated solution for the problem of cleaning glass windowed high rise buildings. It consists of a rollers-based moving platform suspended by a motorized pulley from the top of the building. The cleaning is done with the help of a motor driven cleaning roller brush and water spraying system provided in the platform. The rail system provided on the parapet wall of the building aids in the motorized horizontal movement of the cleaning platform. The entire operation is controlled by a TI MSP430 microcontroller. Once the dimensions of the building are input, the proposed system achieves cleaning with less human intervention. Hence the ASWCS provides an easy, efficient and safe solution for maintenance of skyscraper windows.